Crescimento e desenvolvimento de biótipos de Digitaria insularis resistente e suscetível ao glyphosate - Pereira, Gabriel Rohrer (2015)
The chemical weed management currently applied in the Brazilian and world agriculture, has selected biotypes resistant to herbicides. This selection can change features of the original population of the area, often bringing negative consequences for the area. Given this context, one of the latest cases was biotypes discovery Digitaria insularis resistant to glyphosate. The objective of this study was to identify biotypes resistant to glyphosate and to evaluate the growth and development of these resistant and susceptible biotypes to glyphosate. Biotypes resistant and susceptible were selected in areas with continuous application of glyphosate history, and area without continuous application of glyphosate, respectively. The experiments were conducted at the Experimental Stations Center belonging to Unioeste. The first experiment was conducted to confirm the resistance of the biotypes. The experimental design was a randomized block design with four replications. The treatments consisted of seven doses of glyphosate (0, 180, 720, 1,440, 2,880, 5,760 and 14,400 g ha-1). The application was carried out in the development phase in which the plants had 2 to 5 tillers and 10 cm. The data were submitted to analysis of variance and adjusted to model non-linear regression of sigmoidal type a 3.0 times higher dose of glyphosate to control 50% of biotype resistant plants compared to susceptible biotype was required. It was concluded that there is occurrence of resistance in populations of D. insularis in western Paraná, and the biotype collected in Cascavel, considered resistant. The second experiment was conducted in experimental design of randomized blocks with four replications and 15 treatments, characterized by evaluation times (14, 21, 28, 35, 42, 49, 56, 63, 70, 77, 84, 91, 98 , 105 and 112 days after emergence), at regular intervals of seven days. Biotypes were transplanted into pots with 11 L capacity, one plant per pot each biotype. Leaf area and dry matter evaluations were conducted in 15 seasons. With these data dry matter were calculated relative growth rate (RGR), net assimilation rate (NAR), leaf area ratio (LAR) and leaf weight ratio (RPF). The two biotypes showed similar growth, reaching a maximum leaf area and dry weight to 112 DAE. There was no difference in dry matter accumulation pattern for the biotypes. The TCR and absolute growth rate (TCA) were different for the two biotypes, especially in the early development of plants. The susceptible biotype has higher growth ability when compared resistant, so that the numerical dominance of the resistant biotype compared to susceptible, verified under field conditions, it may be due to caused by herbicide selection pressure